2023
DOI: 10.21203/rs.3.rs-2619781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allogenic stem cells for anal Crohn’s fistula: treating early improves the deep response rate

Abstract: Purpose: The aim of this study was to evaluate the real-life clinical and radiological efficacy of darvadstrocel injection into complex perianal fistulas in Crohn’s disease. Secondary endpoints were to assess symptomatic efficacy, outcomes and factors associated with complete combined clinical-radiological response (deep response). Methods: After marketing the product in France, all patients treated consecutively were included. A complete clinical response was defined by a complete closure of all external open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Dawoud et al 27 treated 14 patients in Austria and achieved a clinical remission of 57%, although again in a small number of patients. Fathallah et al 28 reported on a series of 43 patients treated with darvadstrocel in real-world practice, observing clinical remission in 37% of patients. Recently, they published their clinical and response rate in 27 consecutive patients after 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Dawoud et al 27 treated 14 patients in Austria and achieved a clinical remission of 57%, although again in a small number of patients. Fathallah et al 28 reported on a series of 43 patients treated with darvadstrocel in real-world practice, observing clinical remission in 37% of patients. Recently, they published their clinical and response rate in 27 consecutive patients after 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%